Feasibility and safety of a 6-month exercise program to increase bone and muscle strength in children with juvenile idiopathic arthritis - Kristin M. Houghton; Heather M. Macdonald; Heather A. McKay; Jaime Guzman; Ciarán Duffy; Lori Tucker; on behalf of the LEAP Study Investigators (BMC, 2018)
Abstract Background Arthritis in childhood can be associated with muscle weakness around affected joints, low bone mass and low bone strength. Exercise is recognized as an important part of management of children with juvenile idiopathic arthritis (JIA) but the exercise prescription to best promote bone and muscle health is unknown. We therefore aimed to: 1. assess feasibility and safety of a 6-month home- and group-based exercise program for children with JIA; 2. estimate the effect of program participation on bone mass and strength, muscle function and clinical outcomes and 3. determine if any positive changes in bone and muscle outcomes are maintained 6 months later. Methods We recruited 24 children with JIA who were part of the Linking Exercise, Physical Activity and Pathophysiology in Childhood Arthritis (LEAP) study to participate in a 6-month home-based exercise program involving jumping and handgrip exercises, resistance training and one group exercise session per month. We assessed lumbar spine bone mass (dual energy X-ray absorptiometry), distal tibia and radius bone microarchitecture and strength (high-resolution peripheral quantitative computed tomography), muscle function (jumping mechanography, dynamometry) and clinical outcomes (joint assessment, function, health-related quality of life) at baseline, 6- and 12-months. Adherence was assessed using weekly activity logs. Results Thirteen children completed the 6-month intervention. Participants reported 9 adverse events and post-exercise pain was rare (0.4%). Fatigue improved, but there were no other sustained improvements in muscle, bone or clinical outcomes. Adherence to the exercise program was low (47%) and decreased over time. Conclusion Children with JIA safely participated in a home-based exercise program designed to enhance muscle and bone strength. Fatigue improved, which may in turn facilitate physical activity participation. Prescribed exercise posed adherence challenges and efforts are needed to address facilitators and barriers to participation in and adherence to exercise programs among children with JIA. Trial registration Data of the children with JIA are from the LEAP study (Canadian Institutes of Health Research (CIHR; GRANT# 107535). http://www.leapjia.com/